Analisis Pengaruh Implementasi Rapor Digital dalam Meningkatkan Kualitas Pendidikan di MAN 2 Kota Tanggerang - Uriawan, Wisnu; Mumtaz , Hasna Nabilah; Almubarokah , Luthfiah (UNIVERSITAS SERAMBI MEKKAH, 2025)
Educational institutions must create a management information system that can support a range of operational and managerial tasks in order to raise the caliber of their services. The purpose of this study is to examine how the introduction of digital report cards has affected the standard of instruction at MAN 2 Kota Tangerang. Data was gathered using qualitative research methods, including documentation, interviews, and observation. According to the study's findings, implementing digital report cards can improve the effectiveness of managing student data, but there are drawbacks as well, including the requirement for continuous support, resistance to change, and technical limitations. This study also emphasizes the significance of parents' use of digital report cards and how it affects their participation in their children's education.